ANALISIS EFEKTIVITAS PENGELOLAAN BANTUAN OPERASIONAL SEKOLAH (BOS) PADA SEKOLAH DASAR NEGERI BONIPOI 2 KOTA KUPANG - Sjioen, Alya Elita; Ludji, Stefen Ratu (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2020)
The external evaluation in general primary School Operational Assistance provided funds to create affordable education services and excellent. for all levels of society. One of the factors affecting these programs bos is the management of funds and all available resources in the bos program.The importance of management of the bos funds the primary, with proper management will be able to help ketercapaian bos primary school with the goal of the program is effective and efficient. Effectively and efficiently.The result of this research was boss on the management of public elementary school bonipoi 2 kupang less effective because its not based on technical direction, guidelines this is because the management of bos funds should dikelolah by the school principal And also in the allocation of the cost of bos funds are iain-lain costs that cannot be dijeiaskan in this report answer delivery pertangung often delayed or not timely.